Nurses’ Knowledge, Attitude and Practice Towards Preparedness of Disaster Management in Emergency of Mosul Teaching Hospitals (Medico Legal Update, 2020)
Background: Disasters define as event everywhere in the world every day and have a significant impact onindividuals, families, group and communities.Objectives: The aim of the study was to assessment the nurses’ knowledge, attitude and practice aboutpreparedness of disaster management in emergency of Mosul teaching hospitals/IraqMaterials and Method: In a cross-sectional analysis. The questionnaire consists of (4) main sections:section one demographic date e.g: (age, sex, experience, education level, marital status, and hospitals).Section two included: (47) items related to level of knowledge among nurses about disaster preparedness.Section three consists of (11) elements concern attitude about disaster management. Section four related topractice of regarding disaster management.Results: indicated the finding of the study nurses’ knowledge, attitude and practice about preparedness ofdisaster management in emergency department of Mosul teaching hospitals are highly significant.Conclusion: Through the findings of the study concluded that the awareness or knowledge of nurses is highwith a neutral level of attitude, also practice with respect to disaster preparedness was satisfactory.